Heat Waves in Sarajevo in the Period 1901-2018 - Žiberna, Igor; Drešković, Nusret; Mirić, Ranko (Journal for Geography, 2023)
The article analyzes heat waves in Sarajevo in the period 1901—2018. We presented the trends in the number of heat waves, their length, the highest air temperatures during heat waves and the cumulative highest temperatures during heat waves. We also discussed the trends of the universal thermal climate index for Sarajevo in the period 1961—2018, which show the burdensome thermal effect on humans in a more integral way. In Sarajevo we observe an increase in the number of heat waves, the number of days in heat waves and the cumulative maximum temperatures in heat waves. After 1961, the burdensome thermal effect in the summer months also increases, which also indicates a positive trend in the value of the universal thermal climate index.